Distress during airway sampling in children with cystic fibrosis. Issue 8 (25th May 2018) - Chau, Jun Ting; Peebles, Karen; Belessis, Yvonne; Jaffe, Adam; Doumit, Michael
Abstract : Background: Oropharyngeal suction and oropharyngeal swab are two methods of obtaining airway samples with similar diagnostic accuracy in children with cystic fibrosis (CF). The primary aim was comparing distress between suctioning and swabbing. A secondary aim was establishing the reliability of the Groningen Distress Rating Scale (GDRS). Methods: Randomised oropharyngeal suction or swab occurred over two visits. Two physiotherapists and the child's parent rated distress using the GDRS. Heart rate (HR) was also measured. Results: 24 children with CF, mean age of 3 years, participated. Both physiotherapist and parent rating showed significantly higher distress levels during suction than swab. Inter-rater reliability for the GDRS was very good between physiotherapists, and good between physiotherapist and parents. Conclusion: The study found that oropharyngeal swab is less distressing in obtaining samples than oropharyngeal suction and that the GDRS was reliable and valid.